I'm going to give you an extremal problem.
Given $a_{n}:=\left ( \text{the solution for the equation}\,x^{n}= \cos x,\quad x> 0 \right ),$ find a value of $$\lim_{n\rightarrow\infty}n\left ( 1- a_{n} \right )$$ Source: Fujino_Yusui

If you imagine the graph of $x^{n},$ it should intersect at the point where it increases rapidly by $1,$ which is about where $x^{n}= \cos 1\,(y$ is increasing rapidly, so if you look at $y,$ you should be able to approximate $x$ well enough$).\,n\left ( 1- \cos^{\frac{1}{n}}1 \right )$ looks good, and $\frac{1}{n}= h$ is the derivative of $h\rightarrow 0^{+}.$ I guess $-\ln\cos 1$ by definition.

  • 4
    $\begingroup$ why the tags recursion and recurrence-relations ? $\endgroup$
    – René Gy
    Mar 21, 2021 at 8:29
  • 1
    $\begingroup$ It is my habit. $\endgroup$ Mar 21, 2021 at 8:31
  • 1
    $\begingroup$ @HanulJeon, thanks for your edit, I often don't link the Twitter's account with my post. $\endgroup$ Mar 21, 2021 at 9:29

2 Answers 2


Look at the function $f(x) = x^n - \cos x\implies f'(x) = nx^{n-1}+\sin x > 0$ on $(0,1)$ and $f(0)\cdot f(1) < 0 \implies \exists ! a_n\in (0,1): f(a_n) = 0\implies 0 < a_n < 1$. Next you show $\{a_n\}$ is an increasing sequence ( I leave this for OP to tackle : it will be a good wrestling match for ya ) and you have to use the $x^n = \cos x$ to do it !. After that then it has a limit $L$ and $L = \left(\cos L\right)^{0} = 1$. Thus: $n(1-a_n)= -n(-1+\sqrt[n]{\cos a_n})\to -\ln(\cos 1)$. Note that you can show: $n(\sqrt[n]{L} - 1) \to \ln L, L > 0$


Here is an easy solution.

$x^n=\cos x$, as $a_n$ satisfies the equation, $\left(a_n\right)^n=\cos \left(a_n\right)$

Taking log on both sides,

$n.\log \left(a_n\right)=\log \left(\cos \left(a_n\right)\right)$

$\therefore n=\frac{\log \left(\cos \left(a_n\right)\right)}{\log \left(a_n\right)}$

Now as n tends to infinity, the rhs must also tend to infinity. As cos lies between 0-1, only alternative is that $a_n$ tends to 1. ($a_n=\pi/2$ wil never satisfy the original equation)

$n\rightarrow \infty \therefore a_n\rightarrow 1$

Now we substitute this value of n in our limit,

$\lim _{n\rightarrow \infty }\left(n\left(1-a_n\right)\right)=\lim _{a_n\rightarrow 1}\left(\frac{\log \left(\cos \left(a_n\right)\right)}{\log \left(a_n\right)}\left(1-a_n\right)\right)$

As it is now a 0/0 form, we use the l's hospital, and get the required answer as $a_\infty=-\ln\cos 1$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.